Model Pembiayaan Blended Finance Perbankan untuk Pengembangan Ekowisata Bahari Berbasis Masyarakat (Community-Based Ecotourism) di Kawasan Pesisir Kalimantan Selatan - Ridho Muarief; Rusianto .; Ayu Dewi Mayasari; Muhammad Arif Nurrahman; Andi Nur Patiwi Fatmala (CV. ITTC INDONESIA, 2025)
Community-Based Ecotourism (CBET) in South Kalimantan holds strategic potential within Indonesia’s Blue Economy agenda; however, it continues to face financial exclusion due to various structural constraints such as the absence of formal collateral, unstable seasonal cash flows, and limited managerial capacity within local communities. These conditions lead banking institutions to categorize CBET projects as high-risk and unbankable. This study aims to formulate an adaptive blended-finance model to bridge the mismatch between formal credit requirements and the socio-economic realities of community-based coastal tourism enterprises. The research employed a qualitative descriptive–exploratory approach using in-depth interviews, document studies, and field observations involving 26 informants from the banking sector, local government, tourism community groups (Pokdarwis), venture capital firms, and impact funds. Data were analyzed using thematic analysis through stages of data condensation, data display, and iterative conclusion drawing. The findings indicate that the most relevant financing solution is a tiered blended-finance model, beginning with catalytic funding to strengthen community capacity, followed by impact investment to absorb early-stage risks, and culminating in bank credit during more mature business phases. This model effectively reduces perceived risks among financial institutions, strengthens Pokdarwis governance, and creates a more inclusive financing ecosystem. Thus, blended finance emerges as a strategic instrument for accelerating the sustainable development of CBET in the coastal regions of South Kalimantan.